Reading Habit and Attitude among Filipino Pre-Service English Teachers - Edimar Jausan Sahib (Researchparks Publishing, 2022)
The ability to read is very crucial as it allows individuals to acquire knowledge in various domains of learning. It also influences one’s intellectual and emotional development. Many studies about the reading habit and attitude of the students have already been conducted by researchers across the world. However, no study was found in the context of Zamboanga City. Hence, this present study aims to specifically identify the reading habit and attitude among Filipino Pre-Service English Teachers in Western Mindanao State University. In the conduct of this present study, there was a total of 104 respondents who participated in the final data gathering. For the research design, the study utilized a descriptive quantitative analysis. Moreover, this study used Smith’s (1991) Adult Survey of Reading Attitude (ASRA) that was adapted by Ahmed (2016). This research tool was utilized to collect the responses of the respondents. The results revealed that in terms of reading habits, majority of the respondents (55%) were reported to have spent 1 to 2 hours in reading, 57% preferred online e-books and journals as their reading materials, 47% were found to have spent 3 to 4 hours surfing the internet, 92% preferred reading in English language and 80% of them said yes in reading books each year. Furthermore, when it comes to the respondents’ reading attitude, the results showed that their average mean in Activity of Reading was 3.09 (SD – 0.53) which was interpreted as ‘Moderate Reading Attitude’, their Enjoyment of Reading obtained an mean average 3.67 (SD – 0.72), interpreted as ‘Positive Reading Attitude’, and lastly, their average mean in Anxiety and Difficulty in Reading was 2.46 (SD – 0.59) which was interpret as ‘Negative Reading Attitude’.